2008
DOI: 10.1371/journal.ppat.1000001
|View full text |Cite
|
Sign up to set email alerts
|

A Mycobacterial Enzyme Essential for Cell Division Synergizes with Resuscitation-Promoting Factor

Abstract: The final stage of bacterial cell division requires the activity of one or more enzymes capable of degrading the layers of peptidoglycan connecting two recently developed daughter cells. Although this is a key step in cell division and is required by all peptidoglycan-containing bacteria, little is known about how these potentially lethal enzymes are regulated. It is likely that regulation is mediated, at least partly, through protein–protein interactions. Two lytic transglycosylases of mycobacteria, known as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
153
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(165 citation statements)
references
References 27 publications
8
153
1
3
Order By: Relevance
“…The essential cell wall hydrolase is believed to work in concert with its interacting partner, RpfB, and promote the reactivation process wherein the M. tuberculosis pathogen exits from a non-replicating state to resume active multiplication (36,48). Thus, the ability of MtrB to affect ripA expression via MtrA could be one way of achieving regulated cell wall metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The essential cell wall hydrolase is believed to work in concert with its interacting partner, RpfB, and promote the reactivation process wherein the M. tuberculosis pathogen exits from a non-replicating state to resume active multiplication (36,48). Thus, the ability of MtrB to affect ripA expression via MtrA could be one way of achieving regulated cell wall metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Haiser et al [23] described a related hydrolase of cell wall biosynthesis in Streptomyces coelicolor, indicating the possibility of this class of enzyme be present in Mycobacteriaceae, as observed in our study. Although little is known about the hydrolases in Mycobacteriaceae some authors [24,25] have shown that they may play a role in the late stages of cell division, possibly during re-growth from a stressed state. Additionally, Chauhan et al [24] had proposed previously that the exposure of M. tuberculosis to a variety of DNA damaging agents or certain substances leads to cell division blockage and up regulation of a protein that exhibits cell wall hydrolysis activity, which target the nascent petidoglican synthesis or it may be part of the SOS response in the DNA repair system.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Rpf proteins may be regulated by association with distinct partners. Rubin and coworkers 10,11 reported the interaction between RpfB/E and RipA, a peptidase involved in PG remodeling and cell division. The nature of the interaction is uncertain, however, because the structure of RipA 19 revealed that most of the putative Rpf-interacting segment identified using a yeast two-hybrid assay forms a buried bstrand.…”
Section: The Specialization Of Rpf Proteinsmentioning
confidence: 99%
“…8,9 During growth, the catalytic activity of Rpfs is crucial for cell elongation and division. 10,11 Mtb encodes five Rpf proteins (Rv0867c, Rv1009, Rv1884c, Rv2389c, and Rv2450c named RpfA-E). 12 They are generally predicted to be secreted (RpfA,B,E) or anchored to the membrane (RpfD).…”
Section: Introductionmentioning
confidence: 99%